Polysaccharide from Trichosanthes kirilowii Maxim ameliorates diphenoxylate-induced functional constipation in mice - Jiang, Min; Wang, Chuangchuang; Chen, Jian; Wu, Guozhen; Liu, Wei; Li, Tao; Wang, Xiao (Frontiers in Microbiology, 2025)
IntroductionTrichosanthes kirilowii Maxim has been well-documented for its pharmacological effects in alleviating constipation. Notably, polysaccharides, a class of natural macromolecules, demonstrate significant therapeutic potential for constipation management. Nevertheless, the preventive effect of Trichosanthes kirilowii polysaccharide (TKP) against functional constipation and its underlying mechanisms remain poorly understood.MethodsIn this study, a mouse model of diphenoxylate-induced functional constipation was established. Meanwhile, the laxative effect of TKP on the fecal excretion function, intestinal inflammatory response, neurotransmitter secretion and gut microbiota composition were evaluated.ResultsTreatment with the TKP alleviated the constipation-associated pathological symptoms in mice through enhancing the gastrointestinal (GI) transit ratio and improving defecation function. Moreover, TKP supplementation modulated the secretion levels of neurotransmitters in the serum of mice, elevating excitatory neurotransmitters (SP, MTL and ACH), while suppressing inhibitory neurotransmitters (NO, VIP and ET-1). Additionally, TKP reduced the level of MDA, and enhanced the activities of SOD and GSH-Px, effectively attenuating oxidative stress. Under TKP administration, colonic levels of pro-inflammatory cytokines (IL-6, IL-1β and TNF-α) were significantly suppressed, while upregulating the expression of tight junction proteins (ZO-1 and occludin). Crucially, TKP increased the production of short-chain fatty acids (SCFAs), and modulated the gut microbiota by restoring its abundance and diversity in constipated mice.ConclusionCollectively, these findings demonstrated that TKP could ameliorate diphenoxylate-induced functional constipation in mice, providing a pharmacological foundation for its development as a novel therapeutic agent against constipation.